Potential gross and net N2O production by the gut of different termite species are related to the abundance of nitrifier and denitrifier groups - Miambi, Edouard; Jusselme, Thi My Dung; Châtelliers, Charline Creuzé des; Robert, Alain; Delort, Abigail; Le Roux, Xavier (Frontiers in Microbiomes, 2022)
Termites can be a significant source of N2O emissions in tropical and subtropical ecosystems. The emission rates vary greatly between species, with many species creating emission hotspots while others acting as net sinks. We studied the relationships between net and gross N2O production/consumption and the abundances of eight nitrifier and denitrifier groups (as determined by functional marker genes) in termite gut homogenates for eleven species from five feeding guilds. Overall, the abundance of nitrite reducers and, to a lesser extent, nitrifiers in the gut was strongly correlated with gross N2O production, whereas N2O reduction was correlated with the abundance of nosZ1 N2O reducers and the nosZ1/nirK ratio. Our results show that the differences in gross and net N2O production rates between termite species are primarily due to differences in nitrifier and denitrifier abundances, as well as the ratio of related functional gene marker abundances in the guts. N2O production rates were negatively correlated to the ratio of nosZ to nir. N2O production rates by live individuals measured for a subset of termite species were lower in the wood-feeding than in other species. Our results suggest that the differences in functional gene abundances may be associated with feeding guild, although this should be tested on a larger number of termite species.